2016
DOI: 10.1080/21645515.2016.1203496
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin-rPAc vaccine inhibits biofilm formation but not proliferation ofS. mutans

Abstract: As the main etiologic bacterium of dental caries, Streptococcus mutans (S. mutans) has been considered as the primary object of vaccine research. We previously constructed a recombinant flagellin-rPAc fusion protein (KF-rPAc) that consists of an alanine-rich region to proline-rich region fragment of PAc (rPAc) from S. mutans and flagellin KF from E.coli K12 strain. Intranasal (i.n) immunization of KF-rPAc could induce high level of rPAc-specific antibody responses and offer robust protection against dental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…The present ndings showed that dextransucrase antibody reduced the adherence of S. mutans by 58% as compared to control when grown in presence of 28µg of antibody for 20 hours. These results are similar to the ndings of Huang et al 31 who have reported that S-IgA antibodies reduced signi cantly the adherence of S. mutans in experimental rats. The adherence of S. mutans was also reduced by anti-caries pGJA-P/VAX antibodies as reported by Xu et al 44 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present ndings showed that dextransucrase antibody reduced the adherence of S. mutans by 58% as compared to control when grown in presence of 28µg of antibody for 20 hours. These results are similar to the ndings of Huang et al 31 who have reported that S-IgA antibodies reduced signi cantly the adherence of S. mutans in experimental rats. The adherence of S. mutans was also reduced by anti-caries pGJA-P/VAX antibodies as reported by Xu et al 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Further the uorescence microscopy data also corroborated these ndings of reduction in the bio lm formation in presence of dextransucrase antibody. These observations are in line with the results of antibio lm formation of secretary immunoglobulin A as reported by Huang et al 30 and rPAc-speci c IgG reduced signi cantly bio lm formation in S. mutans challenged rats described by Sun et al 31 Li et al 32 have shown that adherence to tooth surface, bio im formation and growth of S. mutans involves a range of genetic networks which have a signi cant role to interact and coordinate to various environmental signals like surface oxygen, cell density carbon source pH and nutrient availability 33 .…”
Section: Discussionsupporting
confidence: 91%
“…3b ). Then, the quality of the specific antibody responses in the serum and the saliva were tested by an in vitro biofilm formation model, which could indicate the inhibitory efficacy of rPAc-specific antibody responses in samples 34 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum and saliva samples were collected on d 70 and analyzed for KF- and rPAc-specific antibody responses by ELISA as described previously 33 . The biofilm formation inhibition assay was carried out to check the quality of rPAc-specific antibody response in the serum and saliva of immunized mice by biofilm assay as previously described 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant PAc is constructed with the A-region and P-region originating from the PAc protein linked with several amino acids and is utilized more commonly as an immunogen to develop a caries vaccine. This caries vaccine induces specific humoral immunity to inhibit the adherence and colonization of S. mutans on teeth ( 7 ). However, PAc shows low immunogenicity and induces low immune responses that do not maintain adequate protection against dental caries without adjuvants ( 6 , 8 ).…”
Section: Introductionmentioning
confidence: 99%